Communication Strategies of Village Government to Increase Community Participation in Development - Sahid, Muhammad; Haeruddin, Haeruddin; Fitriana, Andi Dian; Wandi, Wandi (Palakka : Media and Islamic Communication, 2025)
This article explores the strategic communication practices employed by the Patangkai Village Government in Bone Regency to enhance community participation in rural development. Situated in the discipline of communication and public administration, the study responds to the need for participatory development approaches that go beyond top-down planning. The research was conducted using a qualitative descriptive method involving in-depth interviews, field observation, and document analysis. Findings indicate that communication strategies—ranging from formal meetings (Musrenbang and Musdes), WhatsApp group messaging, to personalized home visits—play a vital role in shaping community involvement. The study highlights both supporting and inhibiting factors such as leadership transparency, technological access, time constraints, and social hesitancy. While community engagement is gradually improving, challenges remain in reaching marginalized groups and sustaining active participation. The research contributes to the understanding of communication’s function not only as information transmission but as a dialogical and inclusive governance tool. The results emphasize that adaptive and culturally rooted communication strategies are essential for effective participatory development in rural settings. The study concludes that village governments must institutionalize feedback systems and diversify communication approaches to ensure equitable and sustainable engagement. These findings offer practical guidance for local governance and development practitioners.